2007
DOI: 10.1021/je7001094
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Flavonoids in Organic Solvents

Abstract: The solubility of quercetin, isoquercitrin, rutin, chrysin, naringenin, and hesperetin was quantified in acetonitrile, acetone, and tert-amyl alcohol. The solubility was strongly affected by both the nature of the solvent and the flavonoid structure. The highest solubility was obtained in acetonitrile for hesperetin (85 mmol·L-1) and naringenin (77 mmol·L-1) and in acetone (80 mmol·L-1) for quercetin. The lowest solubility value was obtained with rutin in acetonirile (0.50 mmol·L-1). The thermodynamic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(118 citation statements)
references
References 26 publications
6
105
0
7
Order By: Relevance
“…However, it may be noticed that concentration of these substances depends on the polarity of the used solvent. High concentrations in acetone, ethyl acetate and methanolic extracts are the result of high solubility of these metabolites in the solvents, which is consistent with their chemical characteristics [4]. In previous studies, the greatest quantity of total phenolic compounds, including flavonoids, was achieved in acetone extract [5].…”
Section: Discussionsupporting
confidence: 70%
“…However, it may be noticed that concentration of these substances depends on the polarity of the used solvent. High concentrations in acetone, ethyl acetate and methanolic extracts are the result of high solubility of these metabolites in the solvents, which is consistent with their chemical characteristics [4]. In previous studies, the greatest quantity of total phenolic compounds, including flavonoids, was achieved in acetone extract [5].…”
Section: Discussionsupporting
confidence: 70%
“…For instance, the intensity of astragalin and chlorogenic acid spots was higher in 75% ethanol extract than that in 0% extract. The amount of compounds present in the extracts depended on the solubility of compound in the extraction solvent, and since flavonoids have low solubility in water [21] , the increase in the water portion of the extraction solvents would reduce the amount of flavonoids extracted. Although chlorogenic acid was determined as a major chemical constituent in G. procumbens whose concentration depended on the polarity of extracting solvent system and extraction method, it was found that the total phenolic content was the highest in 50% ethanol extract, while chlorogenic acid content was the highest in 75% ethanol extract.…”
Section: Discussionmentioning
confidence: 99%
“…5 Diosmin is considered to be a vascularprotecting agent used to help improving chronic venous insufficiency (CVI), 6 haemorrhoids, lymphedema, and varicose veins. 7 As a flavonoid, diosmin also exhibits anti inflammatory, 8 free-radical scavenging, 9 antidiabetic 10 and antimutagenic properties.…”
Section: -4mentioning
confidence: 99%